Psychological trauma exploration of immigrants on Samuel Selvon’s novels The Lonely Londoners and Moses ascending - Shah, Adeeba Noshin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2021.